Ultra-Wideband Bistatic Radar Measurements of Snow - Omid Reyhanigalangashi; Siva-Prasad Gogineni; Drew Taylor; Shriniwas Kolpuke; Feras Abushakra; Jordan D. Larson; Aabhash Bhandari (IEEE Journal of Microwaves)
This paper presents the development of an ultra-wideband bistatic radar operating over the frequency range of 0.7–2.1 GHz based on the Radio-Frequency System-on-Chip (RF-SoC) platform and its application to snow measurements. The system utilizes Global Positioning System Disciplined Oscillators (GPS-DO) to synchronize the transmitter and receiver mounted on two small unmanned aerial systems (sUAS). We developed an arbitrary waveform generator to synthesize and transmit chirp signals. A data acquisition system was designed to capture signals with up to 2.2 GHz bandwidth and record the radar data. The transmit and receive antennas were developed using a four-element Vivaldi antenna array over the operating frequency range. Bistatic measurements were performed to determine the Brewster angle to estimate snow dielectric properties. The separation, incidence, and reflection angles were adjusted to collect radar data over an angular region extending from 27 to 68 degrees over snow at the Study of Precipitation, the Lower Atmosphere and Surface for Hydrometeorology (SPLASH) field site near Gothic, Colorado.